Website development by nonprofit organizations in an emerging market: a case study of Thai websites. Issue 3 (15th June 2016) - Kirk, Kristin; Ractham, Peter; Abrahams, Alan
Abstract : Nonprofit organizations are pertinent players in making the world a better place. Their websites aid in fulfilling their socially beneficial missions by being a platform to present themselves, to interact with stakeholders around the world, and to perform e‐transactions to raise funds. This interdisciplinary research explores nonprofit websites in Thailand, an emerging market, to determine their progress through an adapted e‐business stage model. A manual website decoding process was used to determine the development of websites, within the sector. On average, almost three‐quarters of the websites offered interactivity and just less than half conducted online transactions, but internationally connected organizations in Thailand were significantly more likely to do so. The findings suggest that while nonprofit websites in Thailand are progressing, there is significant lag between local Thai websites and those that have international connections. While the model successfully provided new data for understanding nonprofit websites in less developed markets, it may need to be modified in future studies. Copyright © 2016 John Wiley & Sons, Ltd.